Life Cycle Assessment of buffalo milk: A case study of three farms in southern Italy. (10th September 2022) - Chirone, Roberto; Paulillo, Andrea; Salatino, Piero; Salzano, Angela; Cristofaro, Brigida; Cristiano, Teresa; Campanile, Giuseppe; Neglia, Gianluca
Abstract: The growing concerns about the relation of livestock activities and sustainability has led to technological progress and the adoption of best practices for reducing their impacts on the environment, including carbon emissions. In southern Italy, farming Mediterranean buffalos for milk production represents a significant portion of the economy. In this study we evaluate the environmental impacts of buffalo milk production using the Life Cycle Assessment approach. The analysis uses a cradle-to-gate system boundaries, an attributional approach and a Functional Unit equal to kg of Energy Corrected buffalo Milk (ECM). We use primary data collected from three farms in Southern Italy, covering a wide range of conditions including organic farming. We investigate the role of allocation method on the overall results and the role of buffalo milk productivity on the environmental impact estimates of milk production. Our results indicate that the environmental impacts of milk production are highly dependent on the chosen allocation method. The life cycle greenhouse gases emission ranges from 1.5 to 2.5 kgCO2eq per kg of ECM, which are slightly larger compared to those of cow milk; this is mainly due to higher milk productivity of cows compared to buffalos. The hot-spot analysis shows that the largest source of climate change impacts are direct emissions from enteric fermentation. The comparative analysis shows that no farm outperforms the other across the entire spectrum of categories and that the milk productivity of buffalos is a key aspect determining the environmental performance of each farm. Graphical abstract: Image 1 Highlights: We use LCA for evaluating the environmental impact of buffalo milk. Organic and conventional milk production were compared. Environmental impacts are highly dependent on allocation method. carbon emissions of buffalo milk are slightly larger than those of cow milk. Organic farm shows larger impact in land use, water use and non-cancer human health.